Flipped Classroom in Post-Pandemic: Evaluating Gender Divide and Impact on the Student’s Achievement in Mathematics - Alviar, Jayson V.; Solon, Leo Jay V. (Future Science / FSH-PH Publications, 2023)
Flipped classroom in mathematics is gaining momentum even in post-pandemic. This innovative pedagogy is beneficial in delivering mathematics content even when the number of learning sessions is reduced due to the restrictions of holding in-person classes. This study explores the effect of flipping mathematics classroom on the achievement of high school students and if a gender divide exists. One-Group Pre-test and Post-test Design was employed. Fifty-seven (57) Grade 10 students were the respondents of this study of which there were twenty-five (25) male and thirty-two (32) female students. Findings revealed that students improved their scores in the given mathematics assessment after being exposed to the flipped classroom. Consequently, the Mean Percentage Scores increased significantly from Low Mastery to Average Near Mastery. However, no gender divide was found in a flipped classroom. Overall, the flipped classroom can potentially increase students’ achievement in mathematics.